Financial Assets, Non-Traded Goods and Devaluation - Kyle, J. F. (Review of Economic Studies, 1978)
Journal Article Financial Assets, Non-Traded Goods and Devaluation Get access John F. Kyle John F. Kyle Imperial Oil Limited, Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 1, February 1978, Pages 155–163, https://doi.org/10.2307/2297091 Published: 01 February 1978